TEACHING IN NON-FORMAL SPACES OF LEARNING IN SÃO GONÇALO- RJ-BRAZIL: A CONSTRUCTION OF GEOGRAPHICAL KNOWLEDGE - RAMOS SACRAMENTO, ANA CLAUDIA; FREITAS HARTMUT BEHM, GUILHERME (Innovare Journal of Education, 2021)
The non-formal spaces of learning have promoted significant experiences to think the teaching of Geography and the spacial understanding of the city. This work has the aims to analyze the importance of spatial understanding of two non-formal spaces located in the municipality of São Gonçalo–RJ-Brazil: the Settlement Farm Engenho Novo–Girassol Site and the Climatological Experimental Station of the State University of Rio de Janeiro. These spaces are visited by students of two public school located in São Gonçalo–RJ-Brazil. The activities guide was built thus to organize the idea of watching, describe, and understanding spaces by students. With the results, the research concludes that the visit to these spaces – as a form of pedagogical didactics - can arouse in students the curiosity, inquiry and the sense of the importance of studying the contents in practice.